Effect of FIO2 on oxidative stress during interval training at moderate atltiude - Wilber, R. L.; Holm, P. L.; Morris, D. M.; Dallam, G. M.; Subudhi, A. W.; Murray, D. M.; Callan, S. D. (Medicine & Science in Sports & Exercise, 2004)
Purpose: To evaluate the effect of different fractions of inspired oxygen (FIO2) on oxidative stress during a high-intensity interval workout in trained endurance athletes residing at altitude.